Adaptive integral terminal sliding mode control for upper-limb rehabilitation exoskeleton - Riani, A.; Madani, T.; Benallegue, A.; Djouani, K. (Control engineering practice, 2018)
A robust adaptive integral terminal sliding mode control strategy is proposed in this paper to deal with unknown but bounded dynamic uncertainties of a nonlinear system. This method is applied for the control of upper limb exoskeleton in order to achieve passive rehabilitation movements. Indeed, exoskeletons are in direct interaction with the human limb and even if it is possible to identify the nominal dynamics of the exoskeleton, the subject’s limb dynamics remain typically unknown and defer from a person to another. The proposed approach uses only the exoskeleton nominal model while the system upper bounds are adjusted adaptively. No prior knowledge of the exact dynamic model and upper bounds of uncertainties is required. Finite time stability and convergence are proven using Lyapunov theory. Experiments were performed with healthy subjects to evaluate the performance and the efficiency of the proposed controller in tracking trajectories that correspond to passive arm movements. •Adaptive integral sliding mode control design for exoskeletons.•Finite time convergence of the closed-loop system.•Robustness of the control law with respect to parametric variations and disturbances.•No requirement of the knowledge of the system bounds.•Real experiments using an upper limb exoskeleton with and without human subjects.